Secular Everyday Life and Religious Sense: Relationship between the Ethical and Religious Spheres - Bacevičiūtė, Danutė (Religija ir kultūra, 2012)
The article deals with the problem of religious sense in the secular everyday life. With reference to Charles Taylor’s analysis of secularization, the author tries to distance herself from the prevailing sociological thesis about the decline of religion in the life of contemporary society and rethink what religion means today? One can notice that “the myth of the Enlightenment” is deeply entrenched in our secular everyday consciousness, so the approach to the religious in the traditional sense is quite aggravated. Nevertheless, such a situation provides a possibility to contemplate the everyday life itself. Derrida’s notion of “religion without religion” allows us to reflect the character of a contemporary religious discourse as well as to envisage the tension between ethical and religious spheres in the daily acts of decision-making, choice, and responsibility. Not traditional religious forms but the structure of religious relationship enables us to talk about religious sense in the secular everyday life.